2021
DOI: 10.3389/fpsyt.2021.721397
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Psychometric Properties of the Chinese Internet Gaming Disorder Checklist (C-IGDC) Among Chinese Adolescents

Abstract: As the first DSM-5 based, multidimensional screening tool of Internet gaming disorder (IGD) designed for Chinese gamers, the Chinese Internet Gaming Disorder Checklist (C-IGDC) has shown satisfactory psychometric properties among Chinese young adults. Given the high vulnerability to IGD among adolescents, the present study aimed to examine the applicability of C-IGDC to Chinese adolescents to address shortfalls in the existing literature regarding the assessment of adolescent IGD screening. Through a two-stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
(67 reference statements)
1
3
0
Order By: Relevance
“…Based on the literature, we specifically selected five validated inventories for the major variables involved in this study. These measures demonstrated good psychometric properties in previous studies among similar populations as the present study [ 3 , 23 , 35 , 45 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ], indicating sufficient suitability to respond to the objectives and questions under investigation. A higher scale score represents a higher level of the corresponding construct.…”
Section: Methodssupporting
confidence: 71%
See 1 more Smart Citation
“…Based on the literature, we specifically selected five validated inventories for the major variables involved in this study. These measures demonstrated good psychometric properties in previous studies among similar populations as the present study [ 3 , 23 , 35 , 45 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ], indicating sufficient suitability to respond to the objectives and questions under investigation. A higher scale score represents a higher level of the corresponding construct.…”
Section: Methodssupporting
confidence: 71%
“…Disordered gaming is a plausible result of maladaptive coping of psychological distress [ 22 ]. Empirical studies have consistently reported that higher levels of psychological distress were positively associated with IGD [ 3 , 23 , 24 , 25 ]. In particular, escapism or avoidance, which are positively associated with IGD tendency [ 26 , 27 ], are often reported as a major motive for online gaming among addicts [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study conducted an item analysis for internal consistency, examined model fit for structural validity and investigated the test-retest reliability of the SAS-SV. Previous studies have demonstrated the test-retest reliability of PSU with a one-month interval [ 29 ], problematic internet use (PIU) with a one-month interval [ 30 ], and internet gaming disorder with two- and three-month intervals [ 31 , 32 ]. We determined that seven- and twelve-month intervals may be justified given that the conditions of behavioral addictions, including internet gaming disorder and gambling disorder, are assessed over the past twelve months in the Diagnostic and Statistical Manual of Mental Disorders (5th ed., Text Revision; DSM-5TR) [ 33 – 35 ].…”
Section: Studymentioning
confidence: 99%
“…Several assessment tools and screening tests based on the diagnostic criteria of IGD were developed following the publication of DSM-5 ( Jo et al., 2018 ; Király et al., 2017 ; Lemmens, Valkenburg, & Gentile, 2015 ; Pearcy, Roberts, & McEvoy, 2016 ; Pontes & Griffiths, 2015 ; Pontes, Király, Demetrovics, & Griffiths, 2014 ; van Rooij, Schoenmakers, & van de Mheen, 2017 ). Some of these have been extensively validated and translated into other languages ( Chen, Su, Dang, & Wu, 2021 ; Király et al., 2017 ; Pontes & Griffiths, 2015 ). One such test, the Ten-Item Internet Gaming Disorder Test (IGDT-10) has been translated into multiple languages, including Japanese ( King et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%